The Jacket - Clement, Andrew (Simon & Schuster, Inc., 2002)
An incident at school forces sixth grader Phil Morelli, a white boy, to become aware of racial discrimination and segregation, and to seriously consider if he himself is prejudiced.
Keywords: Juvenile Fiction / Families / Racism